Evaluating the relationship between single-leg isometric squat and single-leg countermovement jump performance in elite and world-class artistic roller skaters - Rebelo, A.; Lum, D.; Ripley, N.; Comfort, P. (The Journal of Strength and Conditioning Research, 2026)
Lower-limb strength and jump ability are key performance components in artistic roller skating, where athletes perform complex unilateral movements requiring both maximal force and rapid force production. The aim of this study was to evaluate the reliability and practical utility of the single-leg isometric squat for assessing force production and its relationship with performance in the single-leg countermovement jump among elite and world-class artistic roller skaters. Thirty-seven athletes (16 males, 21 females; overall: 17.1 ± 2.6 years, 167.1 ± 10.7 cm, 57.7 ± 10.4 kg; males: 17.5 ± 2.7 years, 175.6 ± 8.3 cm, 64.8 ± 9.5 kg; females: 16.8 ± 2.5 years, 160.6 ± 7.1 cm, 52.4 ± 7.6 kg) performed single-leg isometric squats and single-leg countermovement jumps. Peak force and relative peak force in the single-leg isometric squat demonstrated excellent reliability for both legs (intraclass correlation coefficient [ICC] = 0.96-0.98, coefficient of variation [CV] = 2.56-3.07%), while force at 100 and 200 ms showed moderate-to-good reliability (ICC = 0.82-0.93, CV = 3.88-9.94%). For the single-leg countermovement jump, jump height exhibited excellent reliability (ICC = 0.97-0.98, CV = 5.20-6.44%), while relative propulsive mean force and impulse had moderate-to-good reliability (ICC = 0.83-0.94). Moderate correlations were observed between force at 100 and 200 ms in the single-leg isometric squat and jump height (Pearson's correlation coefficient [r] = 0.45-0.48). Propulsive duration and relative propulsive mean force showed negligible to weak correlations with isometric variables, suggesting that the 2 tests assess distinct aspects of performance. These findings highlight that while the single-leg isometric squat can be used to reliably measure lower-limb strength, its predictive value for dynamic jumping ability is limited because of the weak-to-moderate associations with countermovement jump metrics. However, the test adds value by offering a low-fatigue, safe, and practical method for quantifying unilateral strength capacities over time. This contributes to more informed strength monitoring and individualized program design in artistic roller skating, where unilateral strength is important to performance.